Exploring the interplay between EBV and autophagy-related gene expression patterns in nasopharyngeal carcinoma - Alanazi, Abdullah E.; Awadalla, Maaweya; Alowaini, Amani; Alamri, Saad; AlGhamdi, Doaa Ali; Abdel Halim, Alyaa S.; Ali, Mohamed A. M.; Alosaimi, Bandar (Frontiers in Oncology, 2025)
Introduction/AimWhile components of the autophagy pathway have been linked to cancer prognosis, their relationship with clinical outcomes remains unclear. This study investigates the expression levels of autophagy-related genes (ATGs) at both mRNA and protein levels in nasopharyngeal carcinoma (NPC) and their association with Epstein-Barr virus (EBV) infection, clinicopathological characteristics, and clinical outcomes.Material and MethodsThirty-five formalin-fixed, paraffin-embedded (FFPE) tissue specimens from NPC patients and five non-cancerous nasopharyngeal mucosa control samples were analyzed. Quantitative PCR (qPCR) was used to assess the mRNA levels of nine ATGs, while protein expression was evaluated by immunohistochemistry.ResultsThe results showed that ATG3, ATG4D, ATG4C, ATG4A, ATG2B, and ATG5 expression were significantly higher in EBV-positive NPC, suggesting a notable role of EBV in modulating these genes. Expression of ATG3 and ATG4C proteins was significantly more frequent in EBV-positive NPC patients compared to EBV-negative patients, with a strong correlation between expression of ATG3 or ATG4C and EBV positivity (P = 0.002 for both proteins). Elevated ATG4B and ATG4D expression was significantly associated with reduced distant metastasis in NPC patients (P = 0.019) and within the EBV-positive subgroup (P = 0.014). Reduced ATG4D mRNA levels were also correlated with higher metastasis rates and shorter distant metastasis-free survival (DMFS), highlighting a potential association of ATG4D with DMFS.ConclusionsOverall, these findings emphasize the importance of assessing autophagy-related gene expression as a valuable tool for predicting clinical outcomes in NPC and underscore the need for further research to validate these results and explore therapeutic implications.